Restrictions Placed on Western Culture in Soviet Lithuania in 1965–1986 - Streikus, Arūnas (Genocidas ir rezistencija, 2008)
The research disclosed the controversial tendencies of the Soviet regime’s policy towards cultural ties with the West. On the one hand, during the period under investigation the possibilities to receive Western culture were gradually increasing in Lithuania. More books of fiction were published, more theatre companies and musicians came to Lithuania, and there were more direct ties between Western and Lithuanian intellectuals. More objective publications about Western culture appeared in the print media of Soviet Lithuania. On the other hand, the system of ideological control was promptly adapted to the new situation, which enabled a rather effective control of disseminating Western culture.
Keywords: Western culture; soviet Lithuania; censorship; territory control